(untitled) (Stato, Chiese e pluralismo confessionale, 2019)
SOMMARIO: 1. Chiese autocefale e chiese autonome - 2. La situazione ecclesiastica ucraina - 3. La concessione dell’autonomia nel 1990 alla chiesa ortodossa ucraina - 4. La normativa delle chiese ortodosse circa il conferimento dell’autocefalia - 5. Il ruolo del patriarca ecumenico circa la cura pastorale di quanti fedeli ortodossi vivono nei territori della diaspora - 6. Il ruolo del patriarca ecumenico circa il conferimento dell’autocefalia alla chiesa ucraina - 7. Le obiezioni in linea di diritto e in linea di fatto da parte della chiesa russa - 8. Il tomos dell’autocefalia, prerogative e limiti - 9. Le conseguenze canoniche - 10. La nuova chiesa ucraina autocefala e le altre chiese ortodosse. The autocephaly of the Ukrainian Orthodox Church, doctrinal interpretations and ecclesial structures in comparison ABSTRACT: The granting of the autocephaly to the Ukrainian Orthodox Church has provoked much controversy both with regard to the authority authorized to grant, both regarding the requesting church, and with regard to the involvement of other Orthodox churches with jurisdiction in that territory. In the absence of specific legislation, I took into account the modalities related to the previous concessions and to the subsequent recognition by the other autocephalous churches. The claimed jurisdiction of Constantinople on Ukrainian territory and the objections in law and in fact by the Russian church have been highlighted. From last an indication to the content of the tomos of “autocefalia” and the rights that the ecumenical patriarch is reserved.